2017
DOI: 10.1016/j.nut.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Olive polyphenol effects in a mouse model of chronic ethanol addiction

Abstract: A better understanding of the antioxidant protection provided by polyphenols might be of primary interest for drug discovery and dietary-based prevention of the damage associated with chronic alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…No. DY248) were measured using a sandwich enzyme-linked-immunosorbent assay (ELISA) kits (R&D Systems, Minneapolis, MN, USA), according to the protocols provided by the manufacturer and also according to methods previously described [37][38][39]. Serum samples were diluted 2-and 100-fold with PBS for detection of NGF and BDNF, respectively.…”
Section: Ngf and Bdnf Serum Level Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…No. DY248) were measured using a sandwich enzyme-linked-immunosorbent assay (ELISA) kits (R&D Systems, Minneapolis, MN, USA), according to the protocols provided by the manufacturer and also according to methods previously described [37][38][39]. Serum samples were diluted 2-and 100-fold with PBS for detection of NGF and BDNF, respectively.…”
Section: Ngf and Bdnf Serum Level Evaluationmentioning
confidence: 99%
“…Radicals Test (FORT). FORD and FORT tests were carried out using two specific kits (both purchased by Callegari, Parma, Italy) following the instruction provided by the manufacturer and according to methods previously described [37][38][39]. Blood serum was used both for the FORT and FORD determination.…”
Section: Free Oxygen Radicals Defense (Ford) and Free Oxygenmentioning
confidence: 99%
“…As for the gestational alcohol consumption, the plethora of effects in children induced by ethanol are described as Fetal Alcohol Spectrum Disorders (120)(121)(122)(123). It has also been clearly demonstrated that chronic or binge alcohol consumption as well as alcohol exposure during development may impair brain neurotrophic factors production and the expression of their receptors (124)(125)(126)(127)(128)(129)(130)(131)(132). NGF is one of the most important neurotrophins involved in ethanol-induced toxicity.…”
Section: Ngf and Alcohol-induced Mental Retardationmentioning
confidence: 99%
“…The risk of FASD depends on the amount of ethanol consumed, the frequency of drinking, and the period of pregnancy during which alcohol is consumed as well as the extremely individual conditions of vulnerability to alcohol . Other risk factors include the age of the mother, smoking habit, and poor diet . Safe amounts of alcohol that might be consumed or a safe time to drink during gestation have not been clearly established at the present time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that small amounts of alcohol do not cause gross morphological abnormalities, even though they may induce behavioral and memory impairments and reduced brain volume . Alcohol may easily cross the blood brain barrier and both directly and indirectly may disrupt a developing brain affecting brain cell growth, nervous circuitries, and brain areas physiology by potentiating also oxidative stress . FASD diagnosis is based on several signs and symptoms, and the condition is permanent.…”
Section: Introductionmentioning
confidence: 99%